Electronic phase separation induced non-volatile bi-polar resistive switching in spatially confined manganite microbridges. (24th May 2021) - Jeon, J; Jung, J; Chow, K H
Abstract: Correlated manganite films exhibit functional transport properties due to the co-existence of the competing electronic phase domains which are energetically similar. Here, we investigate very large bi-polar resistive switching (RS) in spatially confined La0.3 Pr0.4 Ca0.3 MnO3 films. In this system, non-volatile bi-polar RS (up to ∼2× 10 6 %) takes place via electric field induced expansion/shrinkage of metallic phase domains, which are separated by an insulating phase domain. These effects are observed without the need of a pre-forming process. We suggest the modification of a memristor model for phase separated systems to explain the observed non-volatile bi-polar I – V characteristics. Investigations of the endurance of the RS over many switching cycles (more than 2.7 × 10 4 switching) show that it does not decay and full switching occurs with a high success rate. Furthermore, the ability to carry out switching between a number of distinct resistance levels is demonstrated.